System for the detection and notification of motorcycle accidents (Machine-translation by Google Translate, not legally binding) - SANTA CARVAJAL, GUADALUPE; PELLICER FERNANDEZ, SOLEDAD; BLEDA TOMAS, ANDRES LORENZO; NACENTA SENZ, JOSE MARIA; MAESTRE FERRIZ, RAFAEL (2018)
System for the detection and notification of accidents in motorcycles that includes a module located on the motorcycle with means to obtain the location of the motorcycle at all times, means to detect the acceleration and inclination of the motorcycle, and means to communicate with other modules of said system, a module with calculation capacity located on the motorcycle with processing means to detect when an accident occurs and with means to communicate with other modules of the system, a portable module and physically separable in two analogous sub-modules with means to make an emergency call and means to communicate with other elements of said system, where if both sub-modules are physically linked behave as a single module and only the means of one of the parts work, and when they are physically separated, the means of both parties independently. (Machine-translation by Google Translate, not legally binding) Sistema para la detección y notificación de accidentes en motos que comprende un módulo ubicado en la moto con medios para obtener la localización de la moto en cada instante, medios para detectar la aceleración y la inclinación de la moto, y medios para comunicarse con otros módulos de dicho sistema, un módulo con capacidad de cálculo ubicado en la moto con medios de procesamiento para detectar cuando se produce un accidente y con medios para comunicarse con otros módulos del sistema, un módulo portable y separable físicamente en dos sub-módulos análogos con medios para realizar una llamada de emergencia y medios para comunicarse con otros elementos de dicho sistema, donde si ambos sub-módulos están unidos físicamente se comportan como un solo módulo y solo funcionan los medios de una de las partes, y cuando están físicamente separadas funcionan los medios de ambas partes de forma independientemente.